Risk factors of severe postpartum hemorrhage in pregnant women with placenta previa or low-lying placenta: a retrospective cohort study - Huiying Hu; Liying Wang; Jinsong Gao; Ziyi Chen; Xiaoxu Chen; Pingping Tang; Yifeng Zhong (BMC, 2024)
Abstract Background The severe postpartum hemorrhage (SPPH) leads to dangerous maternal conditions, and its rate is still increasing and the trend in related risk factors is changing. Placenta-related problems remain the high-risk factor for SPPH. The object is to investigate the prevalence and the risk factors of the severe postpartum hemorrhage in pregnant women with placenta previa or low-lying placenta. Method A retrospective analysis of pregnant women with placenta previa or low-lying placenta after 28 weeks gestation from May 2018 to May 2023 in the Peking Union Medical College Hospital was conducted. The primary outcome was severe postpartum hemorrhage defined as blood loss ≥ 1000 mL within 24 h of childbirth, or with signs or symptoms of low blood volume requiring transfusion of ≥ 4U of red blood cells. Univariate and multivariate logistic regression were used to identify potential risk factors of severe postpartum hemorrhage and receiver operating curve to evaluate the prediction performance. Results Of the 14,964 women, 201 met the inclusive criteria. SPPH rate was 1.3% overall and 18.9% in women with placenta previa or low-lying placenta. Weight (aOR = 0.93, 95%CI 0.87-0.99), increta or percreta placenta (aOR = 7.93, 95%CI 2.53-24.77) were the risk factors. The area under the ROC curve was 0.69(95%CI 0.59-0.80) for increta or percreta placenta alone, and 0.72(95%CI 0.62-0.82) for the combination of times of cesarean sections and anterior placenta. Conclusions Placenta accreta spectrum was the key independent risk factor of SPPH in women with placenta previa or low-lying placenta. Antenatal risk assessment of SPPH in these population is highly desirable and optimal intervention could be planned.